How does radioactive iodine affect the nose?. (12th May 2017) - Server, Ela Araz; Kirgezen, Tolga; Celebi, Ozlem Onerci; Yildiz, Muhammet; Yigit, Ozgur; Cermik, Tevfik Fikret
Abstract : Objectives/Hypothesis: To determine the effect of radioactive iodine (RAI) treatment on the nasal mucosa and nasal functions. Study Design: Prospective clinical study. Methods: This study included 41 patients (31 female and 10 male) who were treated with RAI for papillary thyroid carcinoma. A visual analogue scale (VAS) was used for subjective evaluation of nasal symptoms. The saccharine test, nasal Schirmer test, and acoustic rhinometry were used for objective evaluation of nasal functions. All tests were administered at baseline (before RAI treatment), and then 1 month and 1 year post‐RAI treatment. Only 21 of the patients could be evaluated after 1 year of treatment and were included in the study's analysis. Results: VAS obstruction and dryness scores 1 month and 1 year post‐RAI were significantly higher than the baseline scores ( P < .05 and P < .05, respectively). Mean cross‐sectional area values 1 month and 1 year post‐RAI did not differ significantly from baseline values ( P > .05 and P > .05, respectively). Schirmer test results 1 month and 1 year post‐RAI treatment were significantly lower than at baseline ( P < .05 and P < .05, respectively). Saccharine test results 1 month and 1 year post‐RAI were significantly higher than at baseline ( P < .05). Conclusions: RAI treatment can adversely affect the nasal mucosa. Nasal dryness and obstruction can occur immediately after RAI treatment. Additional research is warranted to further elucidate the effects of RAI treatment on nasal function. Level of Evidence: 4. Laryngoscope, 127:2698–2702, 2017